Glioblastoma-associated microglia reprogramming is mediated by functional transfer of extracellular miR-21 - Abels, Erik R.; Maas, Sybren L. N.; Nieland, Lisa; Wei, Zhiyun; Cheah, Pike See; Tai, Eric; Kolsteeg, Christy-Joy; Dusoswa, Sophie A.; Ting, David T.; Hickman, Suzanne; El Khoury, Joseph; Krichevsky, Anna M.; et al. (Cell Press, 2019)
Gliomas are primary, diffusely infiltrating brain tumors. Microglia are innate immune cells in the CNS and make up a substantial portion of the tumor mass. Glioma cells shape their microenvironment, communicating with and reprogramming surrounding cells, resulting in enhanced angiogenesis, immune suppression, and remodeling of the extracellular matrix. Glioma cells communicate with microglia, in part by releasing extracellular vesicles (EVs). Mouse glioma cells stably expressing a palmitoylated GFP to label EVs were implanted intracranially into syngeneic miR-21-null mice. Here, we demonstrate functional delivery of miR-21, regulating specific downstream mRNA targets in microglia after uptake of tumor-derived EVs. These findings attest to EV-dependent microRNA delivery as studied in an in vivo-based model and provide insight into the reprograming of microglial cells by tumor cells to create a favorable microenvironment for cancer progression.